"See and treat" approach is appropriate in women with high-grade lesions on either cervical cytology or colposcopy - Aue-Aungkul,A. (Asian Pacific Organization for Cancer Prevention, 2015)
This study was undertaken to evaluate the overtreatment rate of women with abnormal cervical cytology undergoing colposcopy followed by loop electrosurgical excision procedure (LEEP), the so-called " see and treat" approach. Overtreatment was defined as LEEP specimens containing cervical intraepithelial neoplasia (CIN) 1 or less. In this study, medical records of 192 women with abnormal Pap smears undergoing the " see and treat" approach in Chiang Mai University Hospital between October 2008 and October 2010 were reviewed. The preceding Pap smears were as follows: 124 (64.6%) with high-grade squamous intraepithelial lesion (HSIL); 35 (18.2%) with atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion (ASC-H); 20 (10.4%) with low-grade squamous intraepithelial lesion (LSIL); 9 (4.7%) with squamous cell carcinoma (SCCA); and 4 (2.1%) with atypical squamous cells of undetermined significance (ASC-US). Histologic results obtained from loop electrosurgical excision procedure (LEEP) were as follows: CIN 2-3, 106 (55.2%); invasive cancer, 41 (21.4%); CIN 1, 15 (7.8%); adenocarcinoma in situ (AIS), 1 (0.5%); and no lesion, 29 (15.1%). Overall, 22.9% of LEEP specimens contained CIN 1 or less. Significant predictors for overtreatment were type of preceding smears and colposcopic impression. If the " see and treat" approach was strictly carried out in women who had either smears or colposcopic findings revealing high-grade disease, the overtreatment rate was only 7%. Hemorrhagic complication was 6.2% and all could be treated at an outpatient department. In conclusion, the overtreatment rate of the " see and treat" approach in women with various degree of abnormal Pap smears is 23% which would be diminished to the acceptable rate of lower that 10% if strictly performed in those with either smears or colposcopic impressions revealing high-grade abnormality. Peri-operative LEEP complications were mild and acceptable.